Experimental and numerical investigation on the optimum distance of a refrigerator from room wall for minimum energy consumption - Abdulwahab, Abdullah Mohamed (2017)
In recent decades, the demand on saving energy and resources has risen to an important limit, in both the industrial and residential sectors. In Malaysia, refrigerators-freezers are considered to be among the largest consumers (26.3%) of residential electricity. The aim of this study was to carry out experimental and numerical investigations to determine optimum distance between the refrigerator and room wall for minimum energy consumption. Furthermore, the influence of air velocity (natural and forced air convection) around the compressor and condenser, frequency of door openings in residential and commercial cases, and different room (kitchen) temperatures, on the energy consumption of the refrigerator were investigated using experimental method. Experiments were carried out on a 150-liter Single-door refrigerator model iR-133C, manufactured in Malaysia. The influence of air velocity on the energy consumption of refrigerator was tested in three scenarios through the experiment. First, as the refrigerator comes from the factory, second by implementing a ventilation system with fan speed of 0.85 m/s, and third with fan speed of 1.65 m/s. Door opening was tested for 60 and 120 times/day in residential and commercial cases respectively through the experiment. In addition, the influence of room (kitchen) temperatures at 25 and 30 °C were also investigated. Distances between the back wall of the refrigerator and the room wall (3, 6, 9, 12, and 15 cm) were applied to the simulation with Malaysian kitchen temperature. The energy consumption was measured through all experiments using FLUKE 345 power quality clamp meter. 3D Computational Fluid Dynamic (CFD) geometries were created using Design Modeler software then, meshed with patch conforming tetrahedral mesh using ANSYS meshing. The simulation was performed using a commercial CFD code FLUENT (ANSYS workbench Version 16.1). The results showed an 8°C decrease in the temperature around compressor compartment within 332.2 Wh/day reduction in the energy consumption of refrigerator was recorded due to 1.65 m/s air velocity. Moreover, 28 % increases stated in the OFF compressor cycle time due to 1.65 m/s air velocity. The results of energy consumption of refrigerator showed 61.2% and 97.1% increases due to door openings for 60 and 120 times/day in residential and commercial scenarios, respectively. In addition, results demonstrated 42 Wh increases in the energy consumption of refrigerator for each 1°C increase in room (kitchen) temperature. The numerical results showed that 12 cm is the optimum distance of refrigerator from room wall for better air flow for the heat that rejected by compressor and condenser. Good agreement was achieved between the numerical and experimental results with 4 % of error. In addition, 26.6 Wh/day reduction in the energy consumption of refrigerator due to place the refrigerator at 12 cm from room wall.